Smaller household size and higher prevalence of serious psychological distress in younger people and never-married people: a nationwide cross-sectional survey in Japan - Tomioka, Kimiko; Shima, Midori; Saeki, Keigo (Frontiers in Public Health, 2024)
Background: Small-member households are increasing worldwide. However, most previous studies have focused on older people and living alone. Using the latest national survey data, we investigated a dose-response relationship between household size and serious psychological distress (SPD).Methods: We analyzed data from the 2019 Comprehensive Survey of Living Conditions in Japan. The study participants were 405,560 community-dwelling adults aged 20 or older. Household size was classified into 5 or more, 3 or 4, two, and one (i.e., living alone).SPD was defined as ≥ 13 points based on the Kessler 6-item Psychological Distress Scale.We used multivariable logistic regressions and included age, education, equivalent household expenditures, housing tenure, employment contract, smoking, and illness under treatment as covariates.Results: After stratified analyses by age and gender, a dose-response relationship between smaller household size and more common SPD was significant for younger, but not for older people (P-trend was < 0.001 in men aged 20-59 and women aged 20-39).After stratified analyses by gender and marital status, a dose-response relationship was significant only for the never-married group in both genders (P-trend was < 0.001 in never-married men and women).Conclusions: Smaller households were associated with higher prevalence of SPD in younger adults and in never-married individuals, regardless of gender. Our findings suggest a need to focus on younger people and never-married people to reduce the mental health risks due to small household sizes.